2013
DOI: 10.1093/gerona/glt149
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Correlates of Sarcopenia in Community-Dwelling Older People: Application of the EWGSOP Definition and Diagnostic Algorithm

Abstract: Sarcopenia identified by the European Working Group on Sarcopenia in Older People criteria is a relatively common condition in Italian octogenarians, and its prevalence increases with aging. Correlates of sarcopenia identified in this study might suggest new approaches for prevention and treatment of sarcopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
163
7
19

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(207 citation statements)
references
References 36 publications
18
163
7
19
Order By: Relevance
“…In a recent application of the EWGSOP criteria for sarcopenia in community-dwelling older people, IGF-1 in the lowest tertile was associated with approximately fourfold higher odds for sarcopenia, a finding that was initially corroborated in our study (Volpato et al 2014). However, subgroup analysis by gender revealed that IGF-1 was associated with sarcopenia only in women, with similar levels being observed in sarcopenic and non-sarcopenic male subjects, although subsequent multiple regression models suggested that the observed influence of IGF-1 in women was largely driven by the effect of age.…”
Section: Discussionsupporting
confidence: 86%
“…In a recent application of the EWGSOP criteria for sarcopenia in community-dwelling older people, IGF-1 in the lowest tertile was associated with approximately fourfold higher odds for sarcopenia, a finding that was initially corroborated in our study (Volpato et al 2014). However, subgroup analysis by gender revealed that IGF-1 was associated with sarcopenia only in women, with similar levels being observed in sarcopenic and non-sarcopenic male subjects, although subsequent multiple regression models suggested that the observed influence of IGF-1 in women was largely driven by the effect of age.…”
Section: Discussionsupporting
confidence: 86%
“…Az első két vizsgált tényező veszélyeztető hatása igazoló-dott, míg a többi három tényező hatása nem bizonyult szignifikánsnak [8]. Volpato az otthon élő idősek kö-rében nem igazolta a jelenlegi fizikai aktivitás, a multimorbiditás és a táplálkozás hatását sarcopeniában, míg az iskolázottság szerepét szignifikánsnak találta [19]. Pong- EREDETI KÖZLEMÉNY chaiyakul kutatása elsősorban a sarcopenia prevalenciájá-ra irányult, a befolyásoló faktorok közül csak a városban élés és a BMI hatását vizsgálta, amelyek szignifikánsnak bizonyultak [17].…”
Section: Megbeszélésunclassified
“…Brazil, japán és koreai populációban 12-22% között mozgott a kimutatott gyakorisági adat [18,31,32]. Olaszországi kutatók tanulmányában a nők 31,6%-a, a férfiak 17,4%-a volt érintett [19]. A cukorbetegségben szenvedő indiai populációban mérték a legnagyobb, 39,5%-os gyakoriságot [33].…”
Section: Megbeszélésunclassified
See 2 more Smart Citations